Aksjologiczne podstawy kategorii rozwój i ich znaczenie dla teorii i praktyki - Piontek, Franciszek (The axiological bases for the category of development and their significance for theory and practice, 2007)
The article shows in a very elear and unambiguous manner the key role and significance of philosophical axiology and the deposit of non-relativized values in defming the category of development and sustainable development as well as in the formulation of the concept of deyelopment realization. Deyelopment is a natural imperative and it cannot be claimed that it is impossible to realize. Additionally, the article indicates that actions related to denying or negating philosophical axiology and the deposit of non-relativized values adversely affect theory and practice. The negative aspects of such actions are a function of the attitude of the institutions listed in the article towards philosophical axiology and the deposit of non-relativized values.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 117-135